PROSPEK PENGEMBANGAN INDUSTRI KECIL TAHU “BAROKAH” DI KELURAHAN OEKEFAN KECAMATAN KOTA SOE KABUPATEN TIMOR TENGAH SELATAN - Deni Junita Selan; Marthen R. Pellokila; Lika Bernadina (Buletin Ilmiah Impas, 2022)
The purpose of this study was to determine the performance of the business, how efficient is the business, and how the prospects for the development of the “Barokah” Tofu Small Industry in Oekefan Village, Soe City District, South Central Timor Regency in the future. The types of data used in this study are primary and secondary data. The results showed that performance analysis was used to determine the type of production produced, marketing and profits in the small industry of "Barokah" tofu. The profit obtained from the small industry of “Barokah” tofu in 2020 is Rp. 951,183,000. The profit is obtained from the total products sold as many as 16,848 tofu boards multiplied by the selling price per tofu board, which is Rp. 110,000 minus the total cost of Rp. 902,097,000. The efficiency value of the "Barokah" tofu small industry in this study is 2.05. Based on the criteria used, this business is efficient because the value of efficiency is more than 1. The results of the calculation of the economies of scale for tofu processing in the small industry of “Barokah” tofu show that the average cost (AC) decreases with increasing business scale. This shows the existence of economies of scale, where a business activity can be said to be an activity with economies of scale.